The Basis For The Judge’s Consideration Of Acquitting The Perpetrators Of Corruption Crime - Anjuandi Saragih; Sohibul Ihsan (Corruptio, 2022)
The decision to release is known as the "vrijspraak" decision in the Continental European family of law. In general, the defendant is released after being found illegally and convincingly guilty of the crime charged by the prosecutor/public prosecutor in the indictment. We can see the acquittal in case Number: 2/Pid/Sus-TPK/2019/PN.Tjk. This study aims to determine the basis of the judge's legal considerations in imposing an acquittal and how the perpetrators of corruption are held accountable. This study uses a qualitative method: data collection techniques by using library research and field studies, which are enriched by interview data sources. Based on the research results, the actions of Defendant Idhamsyah did not meet the elements stated in the Subsidiary indictment by the Public Prosecutor, so the defendant was not legally and convincingly proven guilty of committing a criminal act of corruption. Defendant as PPK did not meet the criteria for the element of "everyone" as stated by the Public Prosecutor, so the element of "everyone" was not fulfilled in the defendant's actions, according to the Panel of Judges. The judge advises dealing with corruption cases to be fair rather than harsh. Judges must consider all aspects of a juridical, philosophical, and sociological nature when deciding a case so that the court's decision falls under the decision of substantive justice.